Pengaruh Penggilingan dan Pembakaran terhadap Kandungan Mineral dan Sifat Fisik Kulit Pensi (Corbiculla Sp) untuk Pakan - . Khalil (Media Peternakan, 2006)
An experiment was conducted to determine the percentage of rate, nutrient contents and physical properties of grinding and roasting products of freshwater mussel shell. Fresh mussel samples were collected from four different lakes in West Sumatra: Maninjau, Singkarak, Danau Diatas and Danau Dibawah. The samples of about 3 kg each were processed to separate the shell and their body content. The shells were then dried and processed to produce three different products: raw coarse ground, raw fine ground and roasted fine ground. Parameters measured included: percent rate of meal, the content of DM, ash, Ca and P, and physical properties (angle of response, bulk and compacted bulk densities and specific density). The results showed that grinding and roasting gave no significant effect on specific density and mineral content of the meal product. The rate of meal product and bulk density decreased, while angle of response and compacted bulk density increased significantly. It was concluded that both roasting and grinding could not improve both nutrient content and physical properties of freshwater mussel shell. Key words : freshwater mussel shell, roasting, mineral composition, physical properties